The recovery and resilience plan on the long-term care system. Towards a deinstitutionalization? - Bermejo-Patón, Fernando; del Pozo-Rubio, Raúl; Amo-Saus, María Elisa; Moya-Martínez, Pablo (Frontiers in Public Health, 2024)
Introduction After the crisis caused by Covid-19, among other socioeconomic problems, the fragility of the organizations that make up the Spanish Long-Term Care System was revealed. These events prompted the Recovery and Resilience Plan (RRP). The aim of this study is to estimate the socioeconomic impact on Long-Term Care (LTC) of the investment delivered by the RRP. In addition, to fulfil our main aim, a secondary and necessary aim was to calculate the most current social accounting matrix (SAM) of the Spanish economy. Methods We analyse the components of the demand linked to the RRP investment allocated to LTC, and subsequently, based on Input–Output methodology, we calculate a social accounting matrix (SAM) of the Spanish economy to estimate the overall economic return. Results The results obtained using the SAM model proposed herein evidence the multiplier effect of the RRP invested in LTC. Every euro allocated to the RRP generates 4 euros in income for Households, Firms and the External Sector, 3.4 euros in industrial output, and returns 0.6 euros in taxes and social contributions to the Government. This also entails creating 26,410 direct and indirect jobs as well as 10,059 induced ones. Discussion Given the severe recession scenario triggered by the consequences of COVID-19, the results of this study highlight the significant multiplier effect that RRP investment may generate to alleviate the downturn in the Spanish economy and, more specifically, in the Spanish LTC System.